Assessing the impact of climate change on groundnut production in Nigeria - Osuji, Emeka (Acta agriculturae Slovenica, 2025)
The study assessed the impact of climate change on groundnut (Arachis hypogaea) production in Ebonyi State, Nigeria. A total of 351 groundnut farmers were purposively selected for the study. Primary data were obtained through structured questionnaires and analyzed using descriptive statistics, multiple regression analysis, and a beta regression model. Climate change had significant adverse effects on groundnut production, including stunted plant growth (P < 0.01), increased pest and disease outbreaks (P < 0.01), and reduced land productivity (P < 0.05). The predominant adaptation strategies employed by farmers were use of improved groundnut varieties (100%), mixed cropping (85.8%), and livelihood diversification (99.1%). Factors significantly influencing adaptation capacity were age (P < 0.01), education (P < 0.01), household size (P < 0.05), and access to capital (P < 0.01). Major constraints to adaptation included inadequate capital (99.7%), distant farmlands (77.2%), and high labor cost (90.8%). The study concludes that climate change poses serious threats to groundnut production and rural livelihoods in Ebonyi State. It recommends increased investment in climate policy financing, establishment of localized climate information centers, and the promotion of climate-smart agricultural practices to strengthen farmers’ resilience and minimize climate-induced losses.
Keywords: adaptation strategies; climate change impacts; gospodinjstva; groundnut production; podnebne spremembe; pridelava arašidov; vplivi